A study of preferred information processing style and its relationship to gender and achievement in the context of design and technology project work - Atkinson, Stephanie (Design and Technology Education: An International Journal, 2008)
One way of raising the efficiency of a scholar’s learning and achievement is to improve teaching strategies employed by staff and the learning strategies adopted by the learner. Teachers have long recognised that learners differ in how they learn and interact with the teaching materials provided for them. However, as Riding (2002) explained, teachers have often lacked a clear means of knowing what these differences were and thereby take account of such differences in their teaching. The research reported in this article attempts to illustrate two of these differences: namely preferred information processing style and gender, and their relationship to achievement in the context of design and technology project work across two phases of education. A smallscale study involving three separate cohorts was used for data collection purposes. Cohort A was made up of 54 students from a university in the North East of England. These students were studying to become secondary school teachers of design and technology. Cohort B was made up of 63 students from a university in the Midlands. In this instance these students were studying to become industrial product designers. Cohort C was made up of 50 Year 10 pupils. These pupils were studying for their GCSE design and technology examination. Data concerning, preferred information processing style, gender and achievement were analysed and the relationship between the selected variables was discussed. Conclusions pertinent to this study were then drawn in the hope that teaching and learning strategies could be improved and that teachers in other institutions may be able to extrapolate from the findings to suit their own situations.